Le système bancaire Algérien à l’heure de l’adhésion à l’OMC - Salima, REKIBA (Sciences humaines, 2014)
Algeria is engaged in the WTO (Ex GATT) accession process since June 1987.This openness and integration  into the international economy choice requires economic and institutional reforms to comply with the rules of the multilateral trading system which Algeria wants to join. We study in this paper the Algerian banking system, the role of the state in the banking market, the reforms undertaken by the government to improve the quality of banking services and increase efficiency in this sector is considered as the hub of economic activity. We address these problems of maladjustment with WTO rules, to which Algeria wants to join .This paper shows the experiences of the privatization of the CPA banking, private banking El Khalifa and experience of installation of foreign banks in the Algerian banking market.   الجزائر انخرطت في مسار الانضمام  إلى المنظمة العالمية للتجارة القات سابقا مند جوان ١٩٨٧ .اختيار الانفتاح والاندماج في الاقتصاد العالمي يتطلب إصلاحات اقتصادية ومؤسساتية للتكيف مع مبادئ المنظمة العالمية للتجارة. ندرس في هدا المقال النظام البنكي الجزائري ودور الدولة الجزائرية فيه وكدا الإصلاحات التي باشرتها لاسيما وإنها تتطلع إلى الانضمام إلى المنظمة العالمية للتجارة كما نتطرق أيضا      إلى تجربة خوصصة القرض الشعبي الجزائري ،تجربة بنك الخليفة وكذا تجربة ولوج البنوك الأجنبية للسوق المصرفي الجزائري.